IMPLIKATUR DAN PELANGGARAN MAKSIM PADA KASUS PELECEHAN ANAK DIMEDIA SOSIAL: KAJIAN PRAGMATIK TUTURAN DALAM VIDEO TIKTOK VENA., S.H - Sefi Diah Arianti; Dwi Wahyu Puspita; Dyah Ayu Fauzyah; Laura Mirpana Rohmah; Nur Lailiyah (Jurnal PENEROKA, 2026)
This study aims to describe the implicatures and politeness maxim violations found in the comment section of TikTok videos uploaded by the account Vena N., S.H., which discuss an alleged case of child sexual abuse. The study is motivated by the free and expressive use of language on social media, which allows users to convey criticism and judgment toward the parties involved in a case. This research uses a descriptive qualitative method with data consisting of utterances containing implicatures and violations of Grice's cooperative principle and Leech's politeness principle. Data were collected through observation and note-taking techniques, then analyzed through reduction, transcription, classification, interpretation, and data presentation. The findings show 20 instances of politeness maxim violations covering the maxims of approbation, sympathy, tact, agreement, and modesty, with the most frequent violations found in the maxims of approbation and modesty. The comments also contain implicatures used to convey criticism, disappointment, and distrust toward law enforcement performance. The most dominant illocutionary function is expressive, followed by representative and directive functions. These findings indicate that although social media provides space for public criticism of legal issues, such criticism is largely expressed through politeness maxim violations and implicatures, suggesting that digital communication tends to prioritize emotional expression over linguistic politeness.